AN ANALYSIS OF THE STUDENTS’ MOTIVATION IN ENGLISH LEARNING AT UPTD SMP NEGERI 4 GUNUNGSITOLI SELATAN IN 2025 - Mince Resti Natalia Hura; Trisman Harefa; Afore Tahir Harefa; Elwin Piarawan Zebua (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
English instruction at UPTD SMP Negeri 4 Gunungsitoli Selatan in 2025. Despite English's global relevance, many students exhibit varying degrees of enthusiasm, limiting their academic commitment and achievement. The primary objectives of this study are to identify intrinsic and extrinsic motivators, analyze their impact on student engagement, and give recommendations to improve the learning experience. Data were collected through a qualitative study methodology that included questionnaires and semi-structured interviews with 29 seventh-grade students. A thematic analysis of the data found that students have a generally positive attitude toward studying English, with key motivators being a desire to communicate with foreigners and further their education abroad. However, obstacles such as pronunciation issues and variable levels of involvement were identified. The findings highlight the value of excellent teaching approaches and supportive peer interactions in creating an engaging learning environment.Student Motivation